Pupils on the move: School catchment area segregation and residential mobility of urban families. (November 2019) - Bernelius, Venla; Vilkama, Katja
Socio-spatial segregation has been recognised as an important factor affecting school segregation and educational attainment in urban schools. As urban populations grow and socio-spatial segregation has become a pressing issue in many contexts, a more sophisticated understanding of the interconnections between spatial and school segregation is needed, including the role of school catchment areas as a possible mediating factor. In our article, we focus on the two-way relationship between urban residential mobility and catchment area segregation in Helsinki, Finland. Using fine-grain statistical data we analyse how the long-term changes in spatial segregation have changed catchment area populations and how residential mobility of families with children is, in turn, related to catchment area composition. The analysis focuses on the majority population whose residential choices typically have the strongest impact on segregation patterns in cities. Our main finding is that there is a systematic relationship between socio-spatial segregation and catchment area differentiation, where the disadvantaged areas are consistently left behind in the general socio-economic development. Even though the institutional school quality is high throughout the city, the residential choices of families with children feed into the self-perpetuating cycles of segregation, as the most disadvantaged areas are rejected and privileged areas favoured in mobility patterns. The results highlight the need for urban educational policies with a high sensitivity to the persistent socio-spatial inequalities shaping educational opportunities.